Impact of the COVID-19 Pandemic on Agriculture in the Visegrad Countries: Results of an Empirical and Econometric Analysis - Suproń Błażej; Łącka Irena (Zagadnienia Ekonomiki Rolnej)
This study aimed to assess the impact of the direct and indirect effects of the COVID-19 pandemic on agricultural production in the Visegrad countries. The study used monthly data for the 2005–2022 period. Based on a literature analysis, key variables affecting agricultural production that were disrupted by the pandemic were identified. In the second step, the FGLS model was used to establish causal relationships between the variables studied and agricultural production. The ARIMA model was then used to determine the difference between the expected and actual production values during the pandemic. The results indicate that variables such as household final consumption expenditure, agricultural exports and imports, and inflation significantly impact agricultural output. At the same time, disruptions in these areas harmed the sector. The analysis indicates that the COVID-19 pandemic, in particular the lockdown policy, led to a permanent loss of agricultural production of 4.5% in the countries studied. Another substantial pandemic effect was high inflation, which shows a non-linear effect on agricultural production. The findings suggest that in the event of similar socio-economic disruptions, policymakers should support domestic consumption of agricultural products and pursue policies that ensure price stability.